Fully-Differential Multifunctional Electronically Configurable Fractional-Order Filter with Electronically Adjustable Parameters - Langhammer, Lukas; Sotner, Roman; Dvorak, Jan; Dostal, Tomas (Elektronika ir Elektrotechnika, 2018)
The paper presents a novel solution of a fully-differential 1+α fractional-order filter. The filter can provide low-pass, high-pass, band-pass and band-stop transfer functions without a necessity of a circuitry change (filter is electronically configurable). The proposed filter also provides the electronic control of its parameters such as the fractional-order of the filter, pole frequency as well as quality factor. Operational Transconductance Amplifiers (OTAs), Adjustable Current Amplifiers (ACAs) and Fully-Differential Current Follower (FD-CFs) were used in the proposal. The proposal is supported by PSpice simulations using transistor-level models of used active elements. DOI: http://dx.doi.org/10.5755/j01.eie.24.5.21841